Acute Effect of Active Tibial Rotation Exercise on Tibial Torsion Angle, Ankle Range of Motion, and Neuromuscular Control - JunHyuk Kim; Kwang-Jin Lee; Keun-Ok An (운동과학, 2023)
PURPOSE This study aimed to analyze the acute effect of active tibial rotation exercise on tibial torsion angle, ankle range of motion, and neuromuscular control. METHODS This study was based on AB/BA Cross-over design, and participants were divided into two conditions (core-tex tibial and manual tibial rotation exercises). Before and after the exercise intervention, tibial torsion angle, non-weight bearing ankle range of motion, weight-bearing ankle range of motion and dynamic balance test, and Shark skill test were conducted. RESULTS An interaction effect was found in the left non-weight-bearing ankle range of motion and the right posterolateral (PL) of the Y Balance Test. In addition, there were significant differences between periods in left tibial torsion angle, non-weight-bearing ankle range of motion, bilateral weight-bearing ankle range of motion, bilateral AN, bilateral posteromedial, right PL, bilateral composite score, and bilateral Shark skill test. CONCLUSIONS Tibial rotation exercise is considered valuable as sports injury prevention training due to its effectiveness for lower extremities functionally and structurally regardless of tibial rotation exercise type.